Notice of Joint Meeting Between the Camarillo and Oxnard Airport Authorities April 12, 2001 (2001)
The agenda for a meeting on April 12, 2001 between the Camarillo Airport Authority and the Oxnard Airport Authority. Discusses the approval of a lease for hangar development at Camarillo Airport, revisions to the five year capital improvement plan, airport noise restrictions, and an Oxnard Airport lease.